Distribution of uidA gene sequences in Escherichia coli isolates in water sources and comparison with the expression of beta-glucuronidase activity in 4-methylumbelliferyl-beta-D-glucuronide media. - Martins, M T (1993)
The uidA gene, which encodes the beta-glucuronidase enzyme, was detected in 97.7% of 435 Escherichia coli isolates from treated and raw water sources by DNA-DNA hybridization; 92.4% of the strains expressed the translational product in 4-methylumbelliferyl-beta-D-glucuronide-containing media after reinoculation. Upon initial isolation from water samples, the minimal medium o-nitrophenyl-beta-D-galactopyranoside-4-methylum-belliferyl -beta-D-glucuronide preparations failed to detect more than 50% of the E. coli isolates that possessed uidA gene. Treated water gave the lowest recovery, with Colilert producing 26% positive samples and Coliquik producing 48% positive samples. There appears to be no relationship between the intensity of the autoradiographic signals of the uidA gene and the expression of beta-glucuronidase activity. Therefore, another variable such as physiological condition of the bacteria could be responsible for the nonexpression of the enzyme activity.